Improving Higher Education Performance in Kenya : A Policy Report - World Bank (World Bank, Washington, DC, 2019)
The report has three main chapters. Chapter two examines the financing situation of the Kenyan higher education system, presents the results of a scenario-building exercise to explore the financial impact of various expansion paths, and proposes a strategy to achieve financial sustainability. Chapter three focuses on the quality and relevance of existing institutions and programs. It starts with an assessment of the present state of Kenyan higher education institutions. It continues with a review of options to strengthen the QA system at the national and institutional levels. Finally, it proposes a road map for developing a well-functioning Labor Market Observatory. Chapter four is a technical note focusing on international developments in the use of technology to increase access and improve quality in higher education. It makes concrete recommendations on how the Kenyan government and university leaders could harness technology in innovative ways.